NEW EDUCATIONAL ENVIRONMENT, TAKING INTO ACCOUNT THE PRINCIPLES OF SUSTAINABLE DEVELOPMENT AND CLIMATE CHANGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article reveals the problems of climate change, which are not just a global trend, but an urgent problem for Kyrgyzstan. The general consequences of climate change for our regionare described. Special attention in the study is paid to the need to develop systematic measures to train and strengthen the potential of young personnel in all areas and raise awareness at all levels ofsociety, the need to introduce climate change courses and adaptation measures into the educational process at all levels.
Keywords: climate change, global warming, adaptation, green economy, sustainable develop- ment, education system.